Palladium Based Microwave Resonant Hydrogen Sensor. Issue 12 (8th September 2022) - Boybay, Muhammed S.; Cicek, Kenan
Abstract: As the surge for renewable and clean energy resources increases, new challenges emerge. One of the challenges related to the use of hydrogen as a clean energy source is safety. In this study, a microwave hydrogen sensor has been presented for detection of hydrogen leakage. An analytical model is developed and the performance of the sensor is investigated using numerical analysis tools. It has been shown that with optimal geometrical parameters of the sensor structure, a wide range of sensitivity levels depending on a wide range of Q‐factor can be achieved. Utilizing a palladium disk with a radius of 750 μm can detect hydrogen with a sensitivity as high as 30 MHz per % hydrogen when g = 10 $g=10$ μm. Average error between analytical model and numerical results is 0.23%. With reference to this work, it is believed that more compact and sensitive microwave hydrogen sensors will be produced for future uses. Abstract : A novel sensor for hydrogen leakage detection is introduced in this work. Inspired by metamaterial‐based sensing modalities, the new sensor combines microwave resonators with palladium based hydrogen sensing. An analytical model is developed for the structure and sensing performance is verified by numerical analysis. A 1% hydrogen concentration change results in 30 MHz resonance frequency shift.